Developmental Perspectives on Arterial Fate Specification - Chen, Dongying; Schwartz, Martin A.; Simons, Michael (Frontiers in Cell and Developmental Biology, 2021)
Blood vessel acquisition of arterial or venous fate is an adaptive phenomenon in response to increasing blood circulation during vascular morphogenesis. The past two decades of effort in this field led to development of a widely accepted paradigm of molecular regulators centering on VEGF and Notch signaling. More recent findings focused on shear stress-induced cell cycle arrest as a prerequisite for arterial specification substantially modify this traditional understanding. This review aims to summarize key molecular mechanisms that work in concert to drive the acquisition of arterial fate in two distinct developmental settings of vascular morphogenesis: de novo vasculogenesis of the dorsal aorta and postnatal retinal angiogenesis. We will also discuss the questions and conceptual controversies that potentially point to novel directions of investigation and possible clinical relevance.